IDENTIFIKASI JAMUR PENYEBAB PENYAKIT PASCAPANEN PADA BIJI JAGUNG DAN KACANG TANAH DI WAKTU PENYIMPANAN - Anggraini, Selviana; Lumbantoruan, Santa Maria; Ansiska, Paisal; Sridanti, Irma Lisa; Vajri, Indri Yanil (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2023)
Pathogens that cause plant diseases do not only attack when it was in the field until harvesting, these attacks continue until the agricultural product was stored and consumed. The agricultural products could be stored for a long period after harvesting. During storage, there were several constraints were found in the form of decreased quality due to postharvest disease which it was caused by several pathogens such as fungi, bacteria, and viruses. Fungi were a group of pathogens that were often found as a cause of postharvest disease in agricultural commodities. The method used in this study was a blotter, then it would be continued by isolation and purification and also identification of the pathogen under a microscope. The results of the identification of fungi that cause postharvest diseases in corn and peanut seeds were found in four pathogenic fungi, namely Aspergillus niger, Aspergillus flavus, Penicillium sp, and Fusarium sp.